Exploring the Performance Improvement of the Oxygen Evolution Reaction in a Stable Bimetal–Organic Framework System - Wang, Xiao‐Li; Dong, Long‐Zhang; Qiao, Man; Tang, Yu‐Jia; Liu, Jiang; Li, Yafei; Li, Shun‐Li; Su, Jia‐Xin; Lan, Ya‐Qian (Angewandte Chemie International Edition, 2018)
Despite wide applications of bimetallic electrocatalysis in oxygen evolution reaction (OER) owing to their superior performance, the origin of the improved performance remains elusive. The underlying mechanism was explored by designing and synthesizing a series of stable metal–organic frameworks (MOFs: NNU‐21–24) based on trinuclear metal carboxylate clusters and tridentate carboxylate ligands. Among the examined stable MOFs, NNU‐23 exhibits the best OER performance; particularly, compared with monometallic MOFs, all the bimetallic MOFs display improved OER activity. DFT calculations and experimental results demonstrate that introduction of the second metal atom can improve the activity of the original atom. The proposed model of bimetallic electrocatalysts affecting their OER performance can facilitate design of efficient bimetallic catalysts for energy storage and conversion, and investigation of the related catalytic mechanisms. An iron atom in an Fe3 cluster is replaced by a second metal to form Fe2M clusters, which can serve as nodes to bridge with organic ligands and construct stable bimetallic MOFs. The introduction of the second metal atom can improve the activity of the original atom and thus improve the oxygen evolution reaction performance of electrocatalysts.